Efektivitas Weed Solut-ioN® sebagai Herbisida Reduktan dalam Pengendalian Gulma di Perkebunan Kelapa Sawit: The Effectiveness of Weed Solut-ioN® as Herbicide Reductant in Controlling Weeds in Oil Palm Estates - Azis Ely; Sofyan Arief (Universitas Widya Gama Mahakam, 2023)
The use of herbicides is one of the most widely used chemicals in the oil palm industry. The chemical that used continuously and in large quantities in oil palm plantation certainly has a negative impact on the environment, especially spray workers who are directly exposed to chemicals. Therefore, it is necessary to find out how to reduce the hazardous from excessive use of chemicals. WEED Solut-ioN® with active ingredient of 2-Sodium Amine is a new product that it is claimed to reduce herbicide doses without reducing its effectiveness. The objective of this trial is to determine the efficacy of herbicide (or cocktails of herbicides) + reductant WEED Solut- ioN® and compared to herbicides (or cocktails of herbicides) (without reductant WEED Solut- ioN®) in controlling weeds in Teladan Prima Agro Tbk. (TPA) estates. The dose treatment of Isopropilamyne glyphosate + Methyl metsulfruron combined with WEED Solut-ioN® (doses 50:50) was not significantly different to control. Other results showed that there was not significantly different between Fluroxipir (with or without sticker) combined with WEED Solut-ioN® (doses 50:50) as well as Ammonium glufosinate combined with WEED Solut-ioN® (doses 50:50). The use of WEED Solut-ioN® (doses 50:50) that are able to reduce the use of herbicide volume can certainly reduce the cost of using herbicides. Keywords: oil palm, weed control, herbicides, reductant, weed solut- ion, cost efficiency